MEMBANGUN KEPUASAN KONSUMEN MELALUI KEPUTUSAN PEMBELIAN - Magenta, Djanur; Sugiarto, Johanes (Faculty of Economics and Business Diponegoro University, 2015)
This study aims to determine how much influence the product, price, location, andpromotion to the buying decision that can build customer satisfaction in stores Essy's Brownies Semarang. This study uses four independent variables are product, price, location, and promotion, customer satisfaction as the dependent variable and the purchase decision as an intervening variable. The population used in this study is that consumers who had visited the shop Essy's Brownies Semarang. This research method using a non-probability sampling technique with accidental sampling method. Used as a sample of 160 respondents. Data obtained from the questionnaires were then processed and analyzed using multiple regression analysis and analysis of SEM (Structural Equation Modeling) through the AMOS program. The results showed that the product has a positive influence on purchasing decisions; price has a positive influence on purchasing decisions; location has a positive influence on purchasing decision; promotion has a positive influence on purchasing decisions; and purchasing decisions have a positive effect on customer satisfaction.